2021
DOI: 10.17993/3ctic.2021.103.121-139
|View full text |Cite
|
Sign up to set email alerts
|

Academic approach about E-learning modules from the teacher/student perspective at the National University Mayor de San Marcos, Lima-Perú

Abstract: The article examines the teacher/student perspective about E-learning modules that could be applied to the courses of the Administration career at the Universidad Nacional Mayor de San Marcos based on 2 methodologies that project a better vision of teaching. To carry out these methodologies, it is necessary to review the results obtained in a survey to determine the factors that influence student learning through the proposed E-learning modules. As a result, 6 factors were obtained to validate whether these E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[12] mentions that considering the COVID-19 pandemic, it is essential to consider citizen participation using web technologies for decision making to improve the services provided. [13] mentions that, after the analysis of the data obtained in the surveys conducted, it is concluded that the factor that most influences virtual learning is the quality of virtual platforms.…”
Section: B Research Backgroundmentioning
confidence: 99%
“…[12] mentions that considering the COVID-19 pandemic, it is essential to consider citizen participation using web technologies for decision making to improve the services provided. [13] mentions that, after the analysis of the data obtained in the surveys conducted, it is concluded that the factor that most influences virtual learning is the quality of virtual platforms.…”
Section: B Research Backgroundmentioning
confidence: 99%
“…According to [8], the lack of technological tools such as online support tools for students, both academic and psychological and everything related to the digital environment, generates impotence in students becomes a key factor of dropout.…”
Section: Student Dropoutmentioning
confidence: 99%
“…Likewise, in online university education, dropout is due to previous academic performance, age, gender, personal circumstances, and self-learning and online learning skills (Orellana et al, 2020). In addition, the lack of technological tools, such as online support tools for students, both academic and psychological, and everything related to the digital environment, generates helplessness in students, becoming a key dropout factor (Saldarriaga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%